2011
DOI: 10.1111/j.1600-0501.2011.02176.x
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy assessment of cone beam computed tomography‐derived laboratory‐based surgical templates on partially edentulous patients

Abstract: The results of this study suggested that laboratory-fabricated surgical guides using CBCT data may be reliable in implant placement under prosthodontic considerations in partial edentulism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
1
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 17 publications
0
29
1
3
Order By: Relevance
“…35 For the present study, we used a sectional cone beam CT scan 36 that can offer some interesting advantages such as comparable level radiation to conventional radiographs, relatively reasonable cost, and the ability to investigate the 3-dimensional image, which is lacking in conventional 2-dimensional radiographs. [37][38][39] Cone beam CT scan proved to be reliable in quantitatively assessing the covering buccal bone thickness in natural teeth with high precision. 40-43 A potential limitation of the study can be the difficulty in measuring the thin buccal plate facing a metallic object such as an implant.…”
Section: Discussionmentioning
confidence: 98%
“…35 For the present study, we used a sectional cone beam CT scan 36 that can offer some interesting advantages such as comparable level radiation to conventional radiographs, relatively reasonable cost, and the ability to investigate the 3-dimensional image, which is lacking in conventional 2-dimensional radiographs. [37][38][39] Cone beam CT scan proved to be reliable in quantitatively assessing the covering buccal bone thickness in natural teeth with high precision. 40-43 A potential limitation of the study can be the difficulty in measuring the thin buccal plate facing a metallic object such as an implant.…”
Section: Discussionmentioning
confidence: 98%
“…15,16,[19][20][21][22][23] In addition, it offers better quality image at low radiation exposure when compared with conventional CT. [24][25][26] It is a suitable noninvasive technique available for assessing the thickness of soft tissue and the underlying bone. 27 The accuracy of CBCT in measuring soft tissue depth measurements has been demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the use of a surgical guide reduces inaccuracies in the transfer of Clin Implant Dent Relat Res. [9][10][11][12] Other factors influencing accuracy were the type of edentulous space, 13 the nature of the remaining teeth, 14,15 the implant system used, 16 and the surgical approach (flap vs flapless 17 or delayed vs immediate placement 18 ). [1][2][3][4] The individual steps of the planning process must be as precise as possible for the sum of the errors to ultimately yield a clinically tolerable discrepancy between the actual and planned implant positions.…”
Section: B Ac Kgr Oundmentioning
confidence: 99%